Aloe Vera Agribusiness Development Sustainability Analysis in Bogor Regency - Sulhajji Jompa; Rizal Syarief; Surjono Hadi Sutjahjo; Anton Yulianto (International Journal of Agriculture System, 2021)
As a suburban area, Bogor Regency faces complex problems in the development of the aloe vera agribusiness. Land use conflicts, unemployment problems due to the Covid-19 pandemic, financial support and market access, post-harvest handling, and institutional support put the sustainability status of this commodity agribusiness into question. This research was conducted to assess the sustainability of aloe vera agribusiness development in Bogor Regency. Analysis of the sustainability status uses the MDS (multidimensional scaling) method, using four dimensions, namely: social, economic, institutional, and environmental. MDS analysis utilizes the Rapid Appraisal for Fisheries (RAPFISH) software. The research was conducted in five sub-districts in Bogor Regency, namely Kemang, Tajur Halang, Rancabungur, Ciampea, and Mount Sindur Districts. The results showed that, in general, aloe vera agribusiness in Bogor Regency has a sustainable status of: "moderately sustainable" (Mount Sindur and Kecamatan Kemang), “close to moderately sustainable" (Rancabungur and Ciampea), and "less sustainable" (Tajur Halang). To support the sustainability status of the aloe vera agribusiness in Bogor Regency,  group land management should be undertaken, assisted by counseling from government institutions, availability of agro-industrial processing, and clarification of land status.